Our own worst enemy? : institutional interests and the proliferation of nuclear weapons expertise - Weiner, Sharon K., 1963- (Belfer Center studies in international security., 2011)
An examination of the effectiveness of knowledge nonproliferation programs implemented by the United States after the fall of the Soviet Union.